Preoperative assessment of liver regeneration using T1 mapping and the functional liver imaging score derived from Gd-EOB-DTPA-enhanced magnetic resonance for patient with hepatocellular carcinoma after hepatectomy - Li, Qian; Zhang, Tong; Yao, Shan; Gao, Feifei; Nie, Lisha; Tang, Hehan; Song, Bin; Wei, Yi (Frontiers in Immunology, 2025)
ObjectivesTo explore whether T1 mapping parameters and the functional liver imaging score (FLIS) based on Gd-EOB-DTPA MRI could evaluate liver regeneration after hepatectomy for HCC patient.MethodsThis retrospective study finally included 60 HCC patients (48 men and 12 women, with a median age of 53 years). T1 relaxation time of liver before gadoxetic acid injection (T1pre) and during the hepatobiliary phase (T1HBP), reduction rate (Δ%) and FLIS were calculated, their correlations with liver fibrosis stage, hepatic steatosis, and liver regeneration, quantified as regeneration index (RI), were assessed by Kendall’s tau-b correlation test or Spearman’s correlation test. Multivariate linear regression analyses were used to explore the indicator of RI.ResultsT1pre, T1HBP, Δ%, and FLIS manifested significant correlation with fibrosis stage (r = 0.434, P =0.001; r = 0.546, P < 0.001; r = -0.356, P =0.005; r = -0.653, P <0.001, respectively). T1pre showed significant correction with steatosis grade (r = 0.415, P =0.001). Fibrosis stage and steatosis grade were associated with RI (r = -0.436, P<0.001; r = -0.338, P =0.008). Accordingly, T1pre, T1HBP and FLIS were the significant predictors (P<0.05) of RI in multivariate analysis. Similarly, in the patients undergoing minor hepatectomy (n=35), T1HBP, Δ% and FLIS were related to RI (P<0.05) in multivariate analysis. Nevertheless, in the patients undergoing major hepatectomy (n=25), no T1 mapping parameter and FLIS was the independent predictor of RI.ConclusionsT1 mapping parameters and FLIS were the potential noninvasive indicators of liver regeneration, except for HCC patients undergoing major hepatectomy.Clinical relevance statementThe value of T1 mapping and FLIS with Gd-EOB-DTPA MRI for accurate preoperative evaluation of liver regeneration is critical to prevent liver failure and improve prognosis of HCC patients.